Chronic pain following mesh repair of inguinal hernia - De zoysa, M.I.M.; Nuzair, M.N.M. (My University, 2012)
The incidence of chronic pain (after 3-6 months) following hernia repair varies from 0.7-36.7% .It is reported to be higher in patients suffering from another painful condition.